Examining the role of Scotland's telephone advice service (NHS 24) for managing health in the community: analysis of routinely collected NHS 24 data. Issue 8 (26th August 2015) - Elliott, Alison M; McAteer, Anne; Heaney, David; Ritchie, Lewis D; Hannaford, Philip C
Abstract : Objectives: To examine the type, duration and outcome of the symptoms and health problems Scotland's nurse-led telephone advice service (NHS 24) is contacted about and explore whether these vary by time of contact and patient characteristics. Design: Analysis of routinely collected NHS 24 data. Setting: Scotland, UK. Participants: Users of NHS 24 during 2011. Main outcome measures: Proportion of the type, duration and outcome of the symptoms and health problems NHS 24 is contacted about. Results: 82.6% of the calls were made out-of-hours and 17.4% in-hours. Abdominal problems accounted for the largest proportion of calls (12.2%) followed by dental (6.8%) and rash/skin problems (6.0%). There were differences in the type of problems presented in-hours and out-of-hours. Most problems (62.9%) had lasted <24 h before people contacted NHS 24. Out-of-hours calls tended to be for problems of shorter duration. Problems reported out-of-hours most commonly resulted in advice to visit an out-of-hours centre and in-hours advice to contact a general practitioner. Most of the service users were female and from more affluent areas. Use of the service declined with age in those over 35 years. The characteristics of users varied according to when NHS 24 was contacted. The number of calls made by an individual in the year ranged from 1 to 866, although most users (69.2%) made only one call. The type of problem presented varied by age and deprivation, but was broadly similar by gender, rural/urban status and geographic area. Call outcomes also varied by user characteristics. Conclusions: This is the first study to examine how the public uses NHS 24. It has identified the patterns of problems which the service must be equipped to deal with. It has also provided important information about who uses the service and when. This information will help future planning and development of the service.